The Interactive E-Module Physical Fitness in Physical Education Learning for Student XI Grade of Senior High School (Journal of Physical Education and Sports, 2022)
The research background was the less optimum of existing teaching material used although the infrastructures were adequate, such as the Internet connection and smart electronic gadgets. The purpose of this research was produces and analyzes an interactive e-module development in learning health, sport, and physical education for XI graders in the material of physical fitness. The researcher used research & development design with nine stages; 1) identification of potentials and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trial run, 7) product revision I, 8) product trial use, and 9) product revision II. The obtained data were quantitative and qualitative. The researchers took the data with expert validation, pretest, posttest, and convenience test of the learners from 5 Public Senior High Schools and 5 Private Senior High Schools. The results of expert validation were obtained with an average percentage of 90%, there was a difference in the average score of pretest and posttest in Public Senior High Schools 41 to 65 and in the Private Senior High Schools from 38 to 61, and the results were significant 0.00 < 0.05. The results and the discussion about the product development showed that: 1) the product, an interactive e-module of physical fitness material for XI graders, was accessible from the link https://bit.ly/PJOKKebugaran_XI via WhatsApp; 2) the product was declared feasible, and 3) the product was effective to use. Researchers suggest that the interactive e-module development in learning health, sport, and physical education for XI graders in the material of physical fitness could widely used.